2012
DOI: 10.1103/physrevb.85.224513
|View full text |Cite
|
Sign up to set email alerts
|

Superfluidity of metastable glassy bulkpara-hydrogen at low temperature

Abstract: Molecular para-hydrogen (p-H 2 ) has been proposed theoretically as a possible candidate for superfluidity, but the eventual superfluid transition is hindered by its crystallization. In this work, we study a metastable noncrystalline phase of bulk p-H 2 by means of the path integral Monte Carlo method in order to investigate at which temperature this system can support superfluidity. By choosing accurately the initial configuration and using a noncommensurate simulation box, we have been able to frustrate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 49 publications
5
45
2
Order By: Relevance
“…1 Intermolecular H 2 -H 2 interactions are attractive and quite intense; hence, even though hydrogen molecules are lighter than 4 He atoms, p-H 2 crystallization is energetically favored over melting in the T → 0 limit frustrating any possibility to observe superfluidity (SF) or Bose-Einstein condensation (BEC) in bulk. Putting this into numbers, molecular hydrogen becomes a solid at temperatures below T t ∼ 14 K, whereas the critical temperature at which BEC and SF are expected to occur is T c ∼ 1 K. 2 In spite of that, many experimental attempts have focused on supercooling bulk liquid p-H 2 below T c , although unfortunately with no apparent success to date. 3,4 A likely way to induce superfluidity in molecular hydrogen consists in lowering its melting temperature by reducing its dimensionality and/or confining it to restricted geometries.…”
Section: Introductionmentioning
confidence: 99%
“…1 Intermolecular H 2 -H 2 interactions are attractive and quite intense; hence, even though hydrogen molecules are lighter than 4 He atoms, p-H 2 crystallization is energetically favored over melting in the T → 0 limit frustrating any possibility to observe superfluidity (SF) or Bose-Einstein condensation (BEC) in bulk. Putting this into numbers, molecular hydrogen becomes a solid at temperatures below T t ∼ 14 K, whereas the critical temperature at which BEC and SF are expected to occur is T c ∼ 1 K. 2 In spite of that, many experimental attempts have focused on supercooling bulk liquid p-H 2 below T c , although unfortunately with no apparent success to date. 3,4 A likely way to induce superfluidity in molecular hydrogen consists in lowering its melting temperature by reducing its dimensionality and/or confining it to restricted geometries.…”
Section: Introductionmentioning
confidence: 99%
“…However, diverse drawbacks such as polydispersity and sedimentation often make the experimental data from these systems difficult to interpret [8,9]. Accessing the details of the crystallization process in simple atomic and molecular counterparts, on the other hand, remains an experimental challenge due to relevant time scales that are orders of magnitude shorter.Theoretical studies have shown that the inclusion of quantum effects adds a further degree of complexity in the behavior of supercooled liquids, leading to novel exotic phenomena such as superfluidity [10,11] or enhanced dynamical slowing down [12][13][14]. Yet again, the difficulties in supercooling a quantum liquid to very low temperatures have so far precluded possible experimental studies of the interplay of quantum effects and structural transformations in nonequilibrium bulk liquids.…”
mentioning
confidence: 99%
“…Theoretical studies have shown that the inclusion of quantum effects adds a further degree of complexity in the behavior of supercooled liquids, leading to novel exotic phenomena such as superfluidity [10,11] or enhanced dynamical slowing down [12][13][14]. Yet again, the difficulties in supercooling a quantum liquid to very low temperatures have so far precluded possible experimental studies of the interplay of quantum effects and structural transformations in nonequilibrium bulk liquids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We used a number of particles and a simulation box with sideratios non-compatible with close-packed crystal lattices; moreover, we generated the starting disordered configuration for our simulations as reported in Ref. 37. The validity of our choices has been checked by computing the probability distributions p(Q 4 ,Q 6 ) for the ordered and disordered configurations, shown in Fig.…”
Section: Appendix: Simulation Detailsmentioning
confidence: 99%